2022
DOI: 10.1002/aelm.202200828
|View full text |Cite
|
Sign up to set email alerts
|

Filament Formation in TaOx Thin Films for Memristor Device Application: Modeling Electron Energy Loss Spectra and Electron Transport

Abstract: Although understanding filament formation in oxide‐based memristive devices by theory has emerged, there are still fundamental unanswered questions. Importantly, for practical application of thin films the material in its amorphous state is to be considered, but mostly lacking so far, and details on sub‐stoichiometry are also scarce. To gain insight into the optical and electronic properties of sub‐stoichiometric amorphous tantalum oxide (TaOx), the electron energy loss spectrum (EELS) of model systems is char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The model of the conductive filament in memristors was proposed according to the first-principles simulations that have been reported elsewhere. The literature found that the principle can be used to predict filament formation, which enables the regulation of operational voltages and improvement in uniformity of memristors, leading to a foundational understanding of performance optimization. , Figure illustrates the probable working mechanism schematic diagram of the fabricated memristor at several different temperatures. Figure a shows conducting filament formation at RT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model of the conductive filament in memristors was proposed according to the first-principles simulations that have been reported elsewhere. The literature found that the principle can be used to predict filament formation, which enables the regulation of operational voltages and improvement in uniformity of memristors, leading to a foundational understanding of performance optimization. , Figure illustrates the probable working mechanism schematic diagram of the fabricated memristor at several different temperatures. Figure a shows conducting filament formation at RT.…”
Section: Resultsmentioning
confidence: 99%
“…The literature found that the principle can be used to predict filament formation, which enables the regulation of operational voltages and improvement in uniformity of memristors, leading to a foundational understanding of performance optimization. 59,60 Figure 9 illustrates the probable working mechanism schematic diagram of the fabricated memristor at several different temperatures.…”
Section: Chemical and Morphological Characterization Of N-eeg And Ti ...mentioning
confidence: 99%
“…TaO x has stable amorphous phase and adaptive lattice rearrangements of oxygen vacancies among metal oxides, which is beneficial to the device's stability. [36,37] The 𝛼-IGZO film serves as an ideal channel layer in thin film transistors due to its high electron mobility. [38] The short-term plasticity and stable, tunable relaxation responses are explored in detail.…”
Section: Introductionmentioning
confidence: 99%